The role of neural cell adhesion molecule in melanoma progression and mesenchymal stromal cells migration - Shi, Yu (2013)
Neural cell adhesion molecule (NCAM), initially characterized in cells from nervous system, has also been found to express in a number of non-neuronal cell types including epithelial cells of various organs and muscle cells. A plethora of evidence have suggested the correlation between deregulated NCAM expression with increased cancer malignancy, however, its implication in melanoma remains elusive. The first part of the thesis aims to unravel the role of NCAM in melanoma progression. To this end, siRNA mediated approach was employed to stably silence NCAM expression in mouse melanoma B16F0 cells. We found that both cellular invasion and metastatic dissemination in vivo were significantly perturbed in the absence of NCAM. We further delineated the underlying molecular mechanism and showed that the pro-invasive function of NCAM was exerted via activation of both cAMP-dependent protein kinase (PKA) and phosphatidylinositol 3-kinase (PI3K) pathways. These two pathways converged at transcription factor cAMP response element binding protein (CREB), which in turn down-regulated mRNA expression of pro-invasive gene matrix metalloproteinase-2 (MMP-2). Together, these findings demonstrated the pro-metastatic function of NCAM thus suggesting the potential implication of anti-NCAM strategy in melanoma treatment. The second part of the thesis consists of studies exploring the role of NCAM in MSCs migration and differentiation. MSCs represent promising tools for cellular therapy owing to their multipotency and ability to localize to injured, inflamed sites and tumor. Various approaches to manipulate expression of MSC surface markers, including adhesion molecules and chemokine receptors, have been explored to enhance homing of MSCs. Recently, NCAM has been found to be expressed in MSCs yet its function remains largely elusive. Herein, we showed that bone marrow-derived MSCs from NCAM deficient mice exhibited defective migratory ability and significantly impaired adipogenic and osteogenic differentiation potential. We further explored the mechanism governing NCAM-mediated migration of MSCs and showed that the interplay between NCAM and fibroblast growth factor receptor (FGFR) induced activation of mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) signaling, thereby the migration of MSCs. In addition, re-expression of NCAM180, but not NCAM140, could restore the defective MAPK/ERK signaling thereby the migration of NCAM-deficient MSCs. Finally, we demonstrated that NCAM180 expression level could be manipulated by pro-inflammatory cytokine Tumor Necrosis Factor (TNF)-α treatment. Overall, our data revealed the vital function of NCAM in MSCs migration and differentiation thus raising the possibility of manipulating NCAM expression to enhance homing and therapeutic potential of transplanted MSCs in cell therapy.